(untitled) (Balneo and PRM Research Journal, 2024)
Background: This study examined the quality of physical therapy services across diverse settings through a cross-sectional correlational analysis. Its fundamental objective lies in exploring the nuanced factors that contextualize the quality of physical therapy practices. (2) Methods: We introduced the Physical therapy Services Evaluation Questionnaire (PSEQ) and gathered patient satisfaction data through a Visual Analog Scale (VAS). The study involved 30 physical therapists (average age 39.57 ± 9.37 years, 40% males and 60% females), assessed via PSEQ, with their work experience (WE) specified. Each physical therapist received feedback from 10 patients using VAS. (3) Results: Following content validation, PSEQ demonstrated strong internal consistency (Cronbach’s alpha coefficient = 0.89). Correlational analyses showed significant positive associations between age and WE, age and PSEQ global score, WE and PSEQ global score, as well as between VAS score and PSEQ global score (p ≤ 0.001). Linear regression analyses confirmed these relationships (p ≤ 0.001) and offered quantifiable basis for predictions, essential for informed decision-making in physical therapy service management and research. (4) Conclusions: The study established robust correlations between physical therapists’ age, WE, and service evaluations. Patient satisfaction, measured through VAS, significantly influences service evaluations, underscoring the importance of continuous professional development and patient-centered care in physical therapy services.